2021
DOI: 10.1371/journal.pone.0259640
|View full text |Cite|
|
Sign up to set email alerts
|

Reasons for nonadherence to vaccination for influenza among older people in Brazil

Abstract: This study aimed to estimate the prevalence of non-vaccination and the reasons for nonadherence to the influenza vaccine among older Brazilians according to sociodemographic characteristics. A cross-sectional study was conducted with data from older people (≥ 60 years of age; n = 23,815) who participated in the 2013 National Health Survey. Frequencies of non-vaccination and the main reasons for nonadherence were calculated with respective 95% confidence intervals. The prevalence of non-vaccination was 26.9% (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…Regarding sociodemographic characteristics, the study found that elderly females had a higher prevalence of vaccination compared to their male counterparts, which is consistent with previous studies 8 , 13 , 14 , 18 - 21 . However, a study carried out in Campinas-SP found a higher prevalence of vaccination against influenza in men 9 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding sociodemographic characteristics, the study found that elderly females had a higher prevalence of vaccination compared to their male counterparts, which is consistent with previous studies 8 , 13 , 14 , 18 - 21 . However, a study carried out in Campinas-SP found a higher prevalence of vaccination against influenza in men 9 .…”
Section: Discussionsupporting
confidence: 91%
“…The main reasons for low vaccination rates reported in the literature include rarely getting the disease, fear of adverse reactions, lack of trust in vaccine efficacy, and not knowing that vaccination is necessary 13,14 . This low adherence may be related to the phenomenon of vaccine hesitation, where individuals delay accepting or refusing recommended vaccines despite their availability in health services [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%